2010
DOI: 10.1056/nejmcibr0912922
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, Gliomas, andIDH1

Abstract: Please be advised that this information was generated on 2020-08-05 and may be subject to change. clinical implications of basic researchT h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 362;12 nejm.org march 25, 2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…GBM, the most aggressive subtype of glioma, has high vascularization and diverse genetic alterations [1, 25, 26]. Given the dismal prognosis of GBM, it would be advantageous to identify early biomarkers of a response to therapy to avoid continuing ineffective treatments and to initiate other therapeutic strategies [1, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…GBM, the most aggressive subtype of glioma, has high vascularization and diverse genetic alterations [1, 25, 26]. Given the dismal prognosis of GBM, it would be advantageous to identify early biomarkers of a response to therapy to avoid continuing ineffective treatments and to initiate other therapeutic strategies [1, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…This ratio is close to the number found in more recent studies 1,8 , which is around 5%. The mutation of IDH-1 seems to point to a slightly better prognosis and perhaps this is the reason to be found more frequently in secondary tumors 8,9,10 . However, in our sample of patients, we found only one case of secondary glioblastoma, which was negative for the mutated form of IDH-1.…”
Section: Discussionmentioning
confidence: 99%
“…of a secondary glioblastoma be positive for this mutation is less than 20% 1,8,9 . The immunostaining for Murine Double Protein 2 (MDM2) was nuclear with an irregular distribution throughout the section.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Since overproduction of this metabolite is associated with a high risk of brain tumors in patients with inborn metabolic errors, the authors concluded that the accumulation of excess 2-hydroxyglutarate in vivo contributes to the formation and malignant progression of gliomas, establishing a link between abnormal metabolism and malignancy. 7 The altered metabolic pathway associat-© F e r r a t a S t o r t i F o u n d a t i o n ed with mutant IDH1 has also been shown to contribute to tumor growth by activating hypoxia-inducible factor-1a. 8 These observations have important clinical implications, as patients with initial or low-grade forms of glioma may benefit from the therapeutic inhibition of 2-hydroxyglutarate production.…”
Section: A Causal Relationship Between Acquired Error In Cellular Metmentioning
confidence: 99%